(untitled) (Revista Científica Integrada, 2023)
Objective: to investigate the effectiveness of dietary interventions in the treatment of endometriosis. Methods: systematic review, conducted in PubMed, Embase, and LILACS databases, and in the AskMEDLINE search tool, in June 2023. The descriptors “endometriosis”, “diet”, “nutrition” and “intervention” were used. The results were limited to primary studies, in English, Portuguese, and Spanish, between 2012 and 2022, which were considered a dietary intervention for the treatment of endometriosis. A bias control was used by two reviewers. Results: 2,044 studies were identified, but only 12 were selected to compose the final sample. Of these, most were randomized controlled trials. Dietary interventions explored the use of vitamins B, C, D, and E, magnesium, resveratrol, fatty acids, N-acetylcysteine, quercetin, restriction, or diet low in fermentable oligosaccharides, disaccharides, monosaccharides, polyols, among others, for the treatment of endometriosis and related symptoms. Conclusion: Dietary interventions show promise in the treatment of endometriosis, although they need to be considered with caution.